Ureteroscopic and Extracorporeal Shock Wave Lithotripsy for Rather Large Renal Pelvis Calculi - Tavakkoli Tabasi, Kamyar; Baghban Haghighi, Mehri (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to compare the results and complications of extracorporeal shock wave lithotripsy (SWL) plus retrograde ureteroscopic lithotripsy using laser and pneumatic lithotriptors with SWL monotherapy for renal pelvic calculi between 2 cm and 3 cm. Materials and Methods: A total of 55 patients with 2- to 3-cm pelvic calculi were assigned into groups 1 and 2, including 22 and 33 patients, respectively. Patients in group 1 first underwent laser pneumatic lithotripsy and insertion of a double-J ureteral catheter and then underwent SWL 2 to 4 weeks thereafter. In group 2, the patients underwent SWL after double-J ureteral catheter insertion. The stone-free rate, complications, and cost effectiveness were evaluated 3 months postoperatively. Results: Five patients (22.7%) in group 1, had their calculi completely fragmented after ureteroscopy and retrograde lithotripsy without any need for further SWL. In 9 patients (40.9%), after a single session of SWL, and in 3 (13.6%), after 2 sessions, fragmentation was completed. In group 2, successful treatment was achieved after 1 and 2 SWL sessions in 6 (18.2%) and 8 (24.2%) patients, respectively. The stone-free rate was significantly higher in the patients of group1 than those in group 2 (77.3% versus 42.4%, respectively; P = .01). The period of anesthesia was 23.1 minutes (during ureteroscopy) in group 1 and 13.2 minutes in group 2 (during cystoscopy or ureteroscopy and insertion of ureteral catheter). No significant complication was reported in neither of the groups. The mean costs of the treatment were US $ 400 and US $ 370 in groups 1 and 2, respectively. Conclusion: Ureteroscopic lithotripsy before SWL is a rational method for the treatment of the rather large renal pelvic calculi with fairly acceptable costs.